Electrotherapy as treatment for chemotherapy-induced peripheral neuropathy — a randomized controlled trial - Sassmann, Robert; Gampenrieder, Simon Peter; Rieder, Florian; Johansson, Tim; Rinnerthaler, Gabriel; Castagnaviz, Vanessa; Lampl, Kathrin; Herfert, Jürgen; Kienberger, Yvonne Theres; Flamm, Maria; Schaffler-Schaden, Dagmar; Greil, Richard (Frontiers in Neurology, 2024)
BackgroundElectrotherapy has been investigated in chronic pain and diabetic peripheral neuropathy, however prospective trials in patients with chemotherapy-induced peripheral neuropathy (CIPN) are scarce.MethodsFifty-one patients with CIPN ≥ grade 1 subsequent to receiving platinum- and/or taxane-based chemotherapy types were randomized to 8 weeks of high tone external muscle stimulation (HTEMS) or transcutaneous electrical nerve stimulation (TENS). The primary outcome were changes in the EORTC-QLQ-CIPN20 questionnaire. Secondary outcomes included clinical examinations, a classification of CIPN according to CTCAE v 4 and the EORTC-QLQ-C30 questionnaire. A control group (n = 17) receiving no intervention was recruited retrospectively.ResultsThe EORTC-QLQ-CIPN20 sensory and motor scales improved in both intervention groups (TENS: −12.3pts and − 8.2pts; HTEMS: −14.7pts and − 8.2pts) with no significant changes in the control group −3.3pts; −2.8pts. The changes in the sensory scale differed significantly between the HTEMS and the control group. In the EORTC-QLQ-C30 questionnaire, there was a significant improvement for physical functioning in the HTEMS group only (+7.9pts) with no between group differences. CIPN classification according to CTCAE v4 improved significantly in both intervention groups.ConclusionHome-based electrotherapy with HTEMS or TENS were successful in improving CIPN-related sensory impairment and could therefore provide a powerful treatment for this side-effect of chemotherapy.Clinical trial registrationhttps://clinicaltrials.gov/ct2/show/NCT03978585